TANTANGAN DALAM PENANGANAN PERKARA TINDAKAN ADMINISTRASI PEMERINTAHAN DI PERADILAN TATA USAHA NEGARA - Hidayat Pratama Putra (Puslitbang Hukum dan Peradilan bekerja sama dengan Ditjen Badimiltun, 2022)
After the enactment of Law Number 30 of 2014 concerning government administration, there are basic things that have impacts on the authority of the administrative court, one of which is governmental real acts. This paper tries to analyze the potential problems that become challenges at the level of implementation of the settlement of cases of “government administrative actions” in the Administrative Court including misunderstanding of the concept of government administrative actions, the accountability regarding administrative tort due to government administrative actions, as well as compensation mechanisms for losses caused by it. Problems were analyzed based on normative legal research methods which were analyzed descriptively. The main challenge in the examination of government administrative actions is that there are many misperceptions about the concept of government administrative actions. Government administration actions are basically real act (Feitelijke handeling) and cannot be interpreted as government actions in a broad sense or known as bestuurshandelingen. Then the concept of accountability for administrative tort in the form of government administrative actions and compensation mechanisms for losses needs to be clarified through laws and regulations because currently there is no standard benchmark regarding the concept of accountability for an administrative tort in the form of government administrative actions, and its compensation mechanisms adequate to the damages for the losses.